2019
DOI: 10.1021/acs.jmedchem.9b00145
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Isoprenylcysteine Carboxylmethyltransferase (ICMT) Inhibitor Improves Survival in Ras-Driven Acute Myeloid Leukemia

Abstract: The requested paper is not presently available in its full-text version for it has not been supplied yet by the researcher in charge of the archiving. * * * *El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Our findings suggested that the 3-amino- N -phenylpropanamide moiety as well as the n -octyl chain of compound 1 were key elements for interaction with ICMT. 20 Accordingly, we envisioned that the phenyl group could be further explored for optimizing cellular viability without significantly compromising ICMT inhibition ( Figure 1 a). This focused library was synthesized as detailed in the Supporting Information .…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggested that the 3-amino- N -phenylpropanamide moiety as well as the n -octyl chain of compound 1 were key elements for interaction with ICMT. 20 Accordingly, we envisioned that the phenyl group could be further explored for optimizing cellular viability without significantly compromising ICMT inhibition ( Figure 1 a). This focused library was synthesized as detailed in the Supporting Information .…”
Section: Resultsmentioning
confidence: 99%
“…Targeting the downstream RAS processing enzymes, namely, RCE1 and ICMT, is an effective approach to prevent the compensation of FTase inhibitors by GGTase in KRAS -mutant tumors. Inhibitors of ICMT, such as cysmethynil and UCM-1336, have been developed and have shown a great capability to reduce KRAS activity and impair the growth of KRAS -mutant cell lines [ 92 , 93 ]. However, the clinical data of ICMT inhibitors in patients with KRAS-mutant CRC are not yet available.…”
Section: Kras Targeting Therapy In Crcmentioning
confidence: 99%
“…The importance of carboxyl methylation for proper membrane localization has been already described for other CAAX proteins, such as Ras [52,53]. In addition, inhibition of ICMT has been described as a promising strategy to inactivate Ras by inducing its mislocalization from the cellular membrane [54][55][56]. In this context, the finding that genetic disruption of ICMT improved the phenotype in the ZMPSTE24 mouse model of progeria supported that a small molecule ICMT inhibitor could represent a new therapeutic strategy to address HGPS.…”
Section: Methylation Inhibitorsmentioning
confidence: 74%